Ratcheting Effects on Regional Government Revenue and Expenditure Budgets in Indonesia - Nyoman Ayu Wulan Trisna Dewi; Nyoman Ari Surya Darmawan; I Gd Nandra Hary Wiguna (Universitas Pendidikan Ganesha, 2023)
This study was conducted to determine the existence of a ratchet effect in the regional revenue and expenditure budget. This research is quantitative descriptive research. The population used in this study were 34 provincial governments in Indonesia. The data used in this study are regional revenue and expenditure budgets data in 2019-2021 from the Ministry of Finance. A simple linear regression model is used to test the research hypothesis. The results of the study found that there was a ratcheting effect in the regional government revenue and expenditure budgets of provincial governments in Indonesia. The results of this study indicate that there is a ratchet effect in the preparation of regional revenue and expenditure budgets. The existence of a ratchet effect in regional revenue and expenditure budgeting implies that the model for setting regional revenue and expenditure budget targets provides incentives for budget actors to behave opportunistically